The syndrome of emotional burnout in oncologists and ways to overcome - Koval, Iryna (Psychosomatic Medicine and General Practice, 2017)
Background. The emotional burnout negatively affects health and professional activity of medical workers. There is a need to improve psychological knowledge and skills, necessary to cope with occupational stress, in medical personnel, especially those, working in oncology. Materials and methods. In the study participated 41 oncologists. We used MBI-HSS questionnaire for the measurement of the burnout manifestations. Results. The severity of emotional exhaustion among oncologists was – 14,8±9,9 points, depersonalization – 5,1±3,7 points and assessment of professional achievement – 36,4±6,7 points. The principal manifestations of emotional burnout in oncologists were feeling of emotional emptiness, anxiety, depressed mood, psycho-emotional and personal detachment, reduced productivity, dissatisfaction with themselves, distancing from patients and colleagues. There were noted some differences in emotional burnout levels in oncologists with different specialization. Although, this differences didn’t reach statistical significance. Conclusion. Development and implementation of the complex psychological program for physicians with psychoeducation and communicative training is a practical solution to emotional burnout problem in oncology.